Change in cardio-protective medication and health-related quality of life after diagnosis of screen-detected diabetes: Results from the ADDITION-Cambridge cohort. Issue 1 (July 2015) - Black, J.A.; Long, G.H.; Sharp, S.J.; Kuznetsov, L.; Boothby, C.E.; Griffin, S.J.; Simmons, R.K.
Highlights We examined individuals with screen-detected diabetes over five years. Two cardio-protective agents were prescribed at diagnosis, 3 at one year and 4 at five years. Increases in cardio-protective medication did not impact negatively on HRQoL.